2022
DOI: 10.1029/2021wr030716
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Grazing by Small Ruminants on Hillslope Hydrological Processes: A Review of European Current Understanding

Abstract: Unsustainable grazing of animals exerts pressure on a range of environmental factors. This review assessed the impacts of grazing of small ruminants (SRs; sheep and goats) on hydrological processes (e.g., runoff occurrence and erosion) within European pasture lands. It also considered other effects of SRs grazing, such as water pollution. Our research highlights the lack of evidence‐based European literature on the implications of grazing by SRs on the hydrological processes. The available literature is limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 198 publications
(348 reference statements)
0
5
0
Order By: Relevance
“…In upland England, OM soils underlie 29% of all rough grassland, 35% of all bracken and 33% of all acid grasslands, and are typically used for livestock grazing (Bol et al, 2011). Although further research is needed to fully assess the influence of grazing on hydrological processes in Europe, current evidence suggests that grazing, especially ‘overgrazing’, likely increases catchment runoff via influence on soils and vegetation (Minea et al, 2022). Field studies have shown that hydraulic conductivity and infiltration rates are lower in areas subject to grazing due to the influence of compaction (Holden, Shotbolt, et al, 2007; Zhao, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In upland England, OM soils underlie 29% of all rough grassland, 35% of all bracken and 33% of all acid grasslands, and are typically used for livestock grazing (Bol et al, 2011). Although further research is needed to fully assess the influence of grazing on hydrological processes in Europe, current evidence suggests that grazing, especially ‘overgrazing’, likely increases catchment runoff via influence on soils and vegetation (Minea et al, 2022). Field studies have shown that hydraulic conductivity and infiltration rates are lower in areas subject to grazing due to the influence of compaction (Holden, Shotbolt, et al, 2007; Zhao, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The urban sewage of this population and residential areas located along the riverbanks is, together with agriculture, one of the main sources of pollution. Moreover, the food industry emissions (mainly from olive oil extraction), along with the diffuse pollution generated by agriculture and livestock, also contribute to river pollution [MINEA et al 2022].…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…Other factors that may influence soil erosion include the removal of vegetation by fire, and animals (Butler, 2007, 2017; Viles, 1988). Animals such as earthworms (Goudie, 1988), gophers (Gabet, 2000; Gabet et al, 2003), monotremes and marsupials (Fleming et al, 2014), rabbits and termites (Humphreys, 1981; Mitchell, 1988), small ruminants (Minea, Ciobotaru, et al, 2022; Minea, Mititelu‐Ionuș, et al, 2022) and badgers (Coombes & Viles, 2015) are recognised biological agents which can turn over large amounts of soil (Wilkinson et al, 2009). These animals influence both soil structure and texture and can allow soil to more easily erode and move downslope in rainfall‐dominated environments.…”
Section: Introductionmentioning
confidence: 99%